Detection of urinary lactoferrin as an indicator of urinary tract infection in girls - Fatah, Mohammed Hassan; Waheda, Nabeel Elia; Kok, Dik J. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Lactoferrin (LF) is an iron-binding protein that is related in structure to transferrin. It is considered to be a part of the innate immune system. This study aimed to assess the role of urinary lactoferrin (LF) as an indicator for diagnosis of urinary tract infection among girls. Methods: This study was conducted on girls suffering from UTI. Urine samples were tested for Lactoferrin before and after two months of the treatment using ELISA technique. Results: Urine specimens were collected from 25 girls with mean age ± SD of 6 ± 3 years without UTI as a control group (C) and 25 girls with mean age ± SD of 5.3 ± 3.18 years diagnosed as suffering from UTI (T1) followed by a set of 25 specimens after two months (T2). The mean concentration of urinary LF ± SD was 670 ± 319 ng/ml in the specimens of control group whereas it was 1387 ± 509 in the specimens of girls with UTI during the infection (T1) and 885 ± 268 after two months (T2). The mean concentrations of urinary LF during the infection (T1) were significantly (P <0.001) increased compared with controls (C) and significantly (P = 0.003) decreased after two months (T2), that may refer to a role of urinary LF in UTI. There was no significant (P = 0.089) difference between the mean concentration of urinary LF after two months (T2) compared with controls (C) that may indicate to the normalization of LF concentration after the treatment synchronously with disappearing of UTI symptoms and significantly reduction of positive urinalysis results. Conclusion: The results of this study indicate the elevation of urinary Lactoferrin (LF) in girls suffering from UTI and probably being a good indicator for diagnosis of UTI.